Allelopathic effects of Jatropha curcas stem extracts on food crops in Tarai area - Rastogi, Akanksha; Singh, Vir (The Indian Journal of Agricultural Sciences, 2020)
Allelopathic effects of Jatropha curcas L. aqueous stem extracts on two varieties each of five food crops, viz. Triticum aestivum (wheat), Zea mays (corn), Oryza sativa (rice), Glycine max (soybean) and Brassica juncea (mustard) were observed in the Tarai area of Uttarakhand in 2017-18. Different concentrations (0%, 5%, 10%, 15% and 20% w/v indicated as T0, T1, T2, T3 and T4, respectively) of Jatrophastem aqueous extract were bio-assayed against germination and seedling growth (plumule and radicle length) of the experimental crops. Significant differences in the normal germination between crops as well as their varieties were observed. Seed germination was significantly reduced (P<0.05) in all crop varieties in all the treatments. However, the reduction was more significant in T4 treatment in all the crops. The Response Index (RI) values ranged from minimum (-0.006) in mustard variety Kranti to maximum (-0.412) in rice variety Govind. The plumule length was significantly reduced (p<0.05) in all the crop varieties and in all the treatments except in T1 treatment. RI values ranged from -0.021 in soybean variety PS-1225 to 0.634 in rice variety Govind at T1 and T4 treatments, respectively. Some crop varieties showed stimulation effect on plumule length, i.e. +0.038 (Govind variety of rice) and +0.237(UP-2526 variety of wheat) at T1 and T2 treatments, respectively. The radicle length was significantly (p<0.05) reduced in all the crop varieties and in all the treatments. Higher concentrations of the stem aqueous extract had a strong inhibitory effect on germination of all varieties.